EFFECTIVENESS OF BODY MAPPING IN IMPROVING KNOWLEDGE ABOUT SEXUAL VIOLENCE PREVENTION IN GRADE 1-2 STUDENTS IN STATE ELEMENTARY SCHOOL (SD) 2 FONTEIN - Dubu, Amalia Marrybeth; Ndun, Helga J. N.; Bunga, Eryc Z. Haba (HEARTY, 2025)
Elementary school children are vulnerable to becoming victims of sexual violence due to the lack of children in getting early sex education. Lack of health education about sexual violence affects children's knowledge, so efforts are needed to improve children's knowledge through health education, namely through health promotion in this study using body mapping media. This study aims to determine the effectiveness of body mapping media in increasing knowledge about preventing sexual violence in grades 1-2 at Elementary School 2 Fontein. This type of research is a pre-experimental design with a one group pretest-posttest design research design. This research was conducted at Elementary School 2 Fontein. The sample in this study was 31 people consisting of 2 classes, namely class 1 totaling 15 students and class 2 totaling 16 students. The data analysis technique used the Wilcoxon Rank Test. The results of this study indicate that body mapping media is effective in increasing students' knowledge about preventing sexual violence with a p value = 0.000 (<0.05). Based on the results of the study, it is hoped that body mapping media can be used as a learning material to increase students' knowledge about sexual violence prevention.